Faktor yang mempengaruhi kejadian anemia pada ibu hamil di Puskesmas Mandrehe Kabupaten Nias Barat - Jairani, Eka Nenni; Gulo, Novtiurlina; Purba, Tuty Hertati; Demitri, Athira; Yulita, Yulita (Journal of Pharmaceutical and Sciences, 2023)
Introduction Anemia in pregnancy is a condition when the hemoglobin (Hb) level is <11 g% in the first and third trimesters, while in the second trimester, the hemoglobin level is <10.5 g%. The implications for pregnant women with anemia are abortion, bleeding during childbirth, low birth weight (LBW) babies, congenital disabilities, and babies easily infected and susceptible to suffering from malnutrition. Objective This study aims to determine the factors associated with the incidence of anemia in pregnant women at Mandrehe Health Center, West Nias Regency. Methods This is an analytical research study using a cross-sectional design. The population in this study was 140 pregnant women, while the sample was 104 pregnant women. The sampling technique was done by proportional random sampling. The data analysis technique used the chi-square test. Results showed that there was a relationship between knowledge and anemia with a p-value of 0.008. There was a relationship between diet and anemia with a p-value of 0.007. There was a relationship between parity and anemia with a p-value of 0.012). There was a relationship between adherence to Fe tablet consumption and anemia with a p-value of 0.000. Conclusion Health workers are expected to provide education to pregnant women about making antenatal care visits during pregnancy. In this way, health workers can monitor the diet, parity, and compliance of pregnant women in consuming blood supplements tablets.